Lectio doctoralis. Jurisdicción constitucional de libertad para la libertad - Ferreira Mendes, Gilmar (2024)
Written version, translated by Carolina Cyrillo, of the oral address given on August 30, 2024, at the awarding of the honorary doctorate from the University of Buenos Aires to Gilmar Ferreira Mendes. Academia. Journal on the Teaching of Law, Year 22, Issue 43, 2024, pp. 73-82. Buenos Aires, Argentina (ISSN 1667-4154) 73